The effect of ampk signaling in type 2 diabetes a literature review - Putri Rahmadhanita; Mgs Irsan Saleh; Eddy Mart Salim (Institute of Computer Science (IOCS), 2023)
Diabetes is a metabolic syndrome characterized by inadequate blood glucose control and associated with reduced quality of life and various complications that significantly shorten life expectancy. Type 2 diabetes is caused by insulin resistance, in which insulin is well secreted but cells do not respond properly. Increasing evidence reveals the role of molecular pathways in the development of DM and its associated complications. The references of this literature review were collected from PubMed. Studies have attempted to identify signaling networks and therapeutic targeting in DM therapy. As the disease progresses, DM is followed by evidence of the existence of a molecular pathway in the form of AMPK signaling which can coordinate cell metabolism according to specific energy needs. AMPK is a master regulator of metabolism that functions to restore energy balance during metabolic stress at both a cellular and physiological level. Inducing AMPK signaling can provide blood glucose in DM which is important to improve hyperglycemia. The purpose of this literature review was to determine the effect of AMPK signaling on type 2 DM and gives an insight about agents that can enhances AMPK signaling to prevent the further impact of DM.